Hypovitaminosis D and Cardiometabolic Risk Factors in Adolescents with Severe Obesity - Teodoro Durá-Travé; Fidel Gallinas-Victoriano; Diego Mauricio Peñafiel-Freire; María Urretavizcaya-Martinez; Paula Moreno-González; María Jesús Chueca-Guindulain (MDPI AG, 2020)
Background/Objectives. Obesity is associated with cardiometabolic risk factors and with Vitamin D deficiency. The aim of this study was to examine the relationship between 25(OH)D concentrations and cardiometabolic risk factors in adolescents with severe obesity. Subjects/Methods. A cross-sectional clinical assessment (body mass index, fat mass index, fat-free mass index, waist-to-height ratio, and blood pressure) and metabolic study (triglycerides, total cholesterol, HDL-C, LDL-C, glucose, insulin, HOMA-IR, leptin, calcium, phosphorous, calcidiol, and PTH) were carried out in 236 adolescents diagnosed with severe obesity (BMI z-score > 3.0, 99th percentile), aged 10.2−15.8 years. The criteria of the US Endocrine Society were used for the definition of Vitamin D status. Results. Subjects with Vitamin D deficiency had significantly elevated values (p < 0.05) for BMI z-score, waist circumference, waist z-score, body fat percentage, fat mass index, systolic and diastolic blood pressure, total cholesterol, triglycerides, LDL-C, insulin, HOMA-IR, leptin, and PTH than subjects with normal Vitamin D status. There was a significant negative correlation (p < 0.05) of serum 25(OH)D levels with body fat percentage, FMI, systolic BP, total cholesterol, triglyceride, LDL-C, glucose, insulin, HOMA-IR, leptin, and PTH. Conclusions. Low Vitamin D levels in adolescents with severe obesity were significantly associated with some cardiometabolic risk factors, including body mass index, waist circumference, fat mass index, high blood pressure, impaired lipid profile, and insulin resistance.